2020
DOI: 10.1136/practneurol-2020-002688
|View full text |Cite
|
Sign up to set email alerts
|

Big data, machine learning and artificial intelligence: a neurologist’s guide

Abstract: Modern clinical practice requires the integration and interpretation of ever-expanding volumes of clinical data. There is, therefore, an imperative to develop efficient ways to process and understand these large amounts of data. Neurologists work to understand the function of biological neural networks, but artificial neural networks and other forms of machine learning algorithm are likely to be increasingly encountered in clinical practice. As their use increases, clinicians will need to understand the basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 24 publications
0
31
0
1
Order By: Relevance
“…Furthermore, without sufficient high-quality training data and robust computational infrastructure, even the most state-of-the-art algorithms are doomed to failure [172]. In general, deep learning algorithms require large volumes of data to train the AI systems at the best level to obtain the best results.…”
Section: Solutions Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, without sufficient high-quality training data and robust computational infrastructure, even the most state-of-the-art algorithms are doomed to failure [172]. In general, deep learning algorithms require large volumes of data to train the AI systems at the best level to obtain the best results.…”
Section: Solutions Limitations and Future Directionsmentioning
confidence: 99%
“…Despite the efforts to standardize patient care, the variability between patients concerning differences in clinical presentation and desired outcomes should be thoroughly considered prior to AI model development [173]. Any potential deviation from the training conditions may result in the unpredictable behavior of an algorithm [172].…”
Section: Solutions Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases ML models do not generalize to new data, thus leading to large errors on the test set, limiting the usefulness of the study. Further explanations of these terms have been recently provided, with examples, in the field of neurology [25], while some widely-used methods are explained in Section 5.…”
Section: What Can Be Gained From Machine Learningmentioning
confidence: 99%
“…Inspection of the results of a PubMed search with keywords "multiple sclerosis" AND ("machine learning" OR "artificial intelligence" OR "neural network") retrieved 286 studies, of which eight used clinical data to derive predictions on the course of MS in individual patients. The papers are listed in Table 1, together with one work identified among the references cited by another review [25]. No additional studies were found among the first 100 results (ranked by relevance) of an identical search performed on Google Scholar, which yielded 3980 results.…”
Section: Clinical Datamentioning
confidence: 99%